202 VARIABILITY OF HUMAN SERA FOR SURFACTANT INACTIVATION. (1st January 2005) - Iwanicki, J. I.; Matthay, M. A.; Lu, K. W.; Taeusch, H. W.
Abstract : The treatment of acute respiratory distress syndrome (ARDS) has proven to be challenging; patients do not respond effectively to standard pulmonary surfactant treatment. Due to increased capillary permeability in the alveoli of patients with ARDS, serum proteins are able to leak into the alveolar space where they lead to pulmonary surfactant inactivation. While some ubiquitous proteins that inactivate surfactant have been identified, such as albumin and fibrinogen, it has yet to be determined why some people with lung insults go on to develop ARDS and others do not. It is hypothesized that there is variability among human sera in the capacity to inactivate pulmonary surfactant, and that those people susceptible to ARDS have sera that have a greater capacity to inactivate surfactant than those people who are not susceptible to ARDS. Serum samples were collected from five human volunteers with no lung injury, and the strength of their ability to inactivate Infasurf was measured using a trough filled with a mixture of an individual's serum extract and buffer. Surfactant was added to the surface of the mixture, and the surface tension measured with a metal wire. It was found that the differences in surfactant inactivation amongst healthy individuals were statistically significant (p≤ 0.01). This implied that there might indeed be differences in the susceptibility of different individuals to developing ARDS. If the initial hypothesis were correct, we would expect to see variability in the surface tensions measured among the sera of unaffected subjects. Banked serum samples of eight patients with ARDS were obtained, in addition to banked serum samples from six patients with hydrostatic pulmonary edema. These sera inhibitory capacities were measured using, and it was found that there was no significant statistical difference between the two groups, nor between the banked samples and the sera of healthy volunteers. Several possible explanations exist for this unexpected outcome—there really is no difference between the sera of those who develop ARDS and those who do not, and the cause of the disease lies elsewhere (extent of injury, other preexisting conditions, etc.); there may be differences between individual key components of sera, but they are overshadowed by other sera components; there normally is a difference between the two groups, but during ARDS a large amount of key components leak into alveoli (via the selective permeability of the alveolar capillaries), leaving lower serum levels.